Factors affecting Uptake of Post Natal Care Services among Postnatal Mothers in Lira Regional Referral Hospital, Lira City. A Cross-sectional Study. - Emmanuel Abraham Akiki; Sania Nakasolo (Student's Journal of Health Research, 2022)
Background: Postnatal care is defined as care given to the mother and her newborn baby immediately after the birth of the placenta and for the first six weeks of life, the objective of this study is to determine the individual factors, assess the health facility-related factors, and determine the community-related factors affecting the uptake of PNC services among postnatal mothers in Lira Regional Referral Hospital, Lira City. Methods:  A descriptive cross-sectional research design was used, with quantitative methods of data collection. A sample of 50 respondents who were postnatal mothers with children less than 2 months of age were used, selected by simple random sampling. Data was collected using researcher-administered questionnaires and analyzed using a descriptive method presented on graphs, tables, figures, and charts. Results:  Less than half (42%) of the respondents are 5 to 7 km from the health facility, the majority (64%) of the respondents got routine health education, and the majority (74%) of the respondents reported that they took less than one hour to reach the nearest health facility, most (52%) of the respondents have ever been visited at home, the majority (62%) of the respondents do not have cultural practices about PNC, most (66%)of the mothers delivered from the health facility, the majority (68%) of the mothers were from low poverty level communities and finally, most (64%) of the mothers were from urban areas. Conclusion:  There was high uptake of PNC among mothers who resided nearer to the health facility, and got routine health education than those working. Recommendations:  There is a need to encourage community awareness of the available PNC services, there is a need to provide routine health education, there is a need to encourage husband involvement in health care and finally, there is a need to reduce community poverty levels.